The impact of creative learning environments on learners: A systematic literature review. (March 2013) - Jindal-Snape, Divya; Davies, Dan; Collier, Chris; Howe, Alan; Digby, Rebecca; Hay, Penny
This article is based on a systematic review of educational research, policy and professional literature relating to creative environments for learning in schools. Despite the search yielding 210 documents, comparatively few empirical studies were published between 2005 and 2011 that addressed the review objectives. Only 18 studies included in the review investigated the impact of creativity on learners. There was, however, some evidence for the impact of creative learning environments on pupil attainment, confidence, resilience, motivation, problem-solving, interpersonal skills and school attendance. These findings have implications for policy, practice and research internationally.